JETT 2022
DOI: 10.47750/jett.2022.13.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The application of translation strategies and predicate transformations in teaching written translation

Abstract: The aim of the article was to investigate the impact of the context and instructions on the situation during written translation. In particular, there was an objective to clarify two aspects: pragmatic (preservation of the pragmatics of the original in the translation, taking into account the task) and syntactic (the impact of changing the syntax on the correctness of the translation). The following methods were used: contextual analysis of discourse, description, classification, observation. Experimental rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Many studies conducted in this field including ; An, J., & Sun, J. (2022), Curran, et al (2022), Francisco-Velilla, et al (2022, Ginting (2022), Hrytsanchuk (2022), Jameel (2022), Li, et al (2022), Saha and Mandal (2022), Giroux, et al (2021), Anber and Jameel (2020), Iglikova and Usataya (2019), and Leni and Pattiwael (2019), showed that using the appropriate translation strategy is the key of successful translation and delivering précis and accurate information in a scientific style. This study tries to enrich the Iraqi literature concerning the translation strategies that the EFL students use in translation and the quality of the translation from English into Arabic or vice versa.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Many studies conducted in this field including ; An, J., & Sun, J. (2022), Curran, et al (2022), Francisco-Velilla, et al (2022, Ginting (2022), Hrytsanchuk (2022), Jameel (2022), Li, et al (2022), Saha and Mandal (2022), Giroux, et al (2021), Anber and Jameel (2020), Iglikova and Usataya (2019), and Leni and Pattiwael (2019), showed that using the appropriate translation strategy is the key of successful translation and delivering précis and accurate information in a scientific style. This study tries to enrich the Iraqi literature concerning the translation strategies that the EFL students use in translation and the quality of the translation from English into Arabic or vice versa.…”
Section: Statement Of the Problemmentioning
confidence: 99%